Educating the Educators: Socialization into the Teaching Profession - O'Toole, Roger (My University, 1966)
The study attempts to examine some of the "professional” attitudes and values of elementary school teaching as an occupation, by means of a study of the socialization process in a Teachers’ College, It is contended that sociological study of the professions would benefit by utilisation of a '’conspiracy theory” and the study attempts partly to estimate the usefulness of this theory with respect to teaching, Sociologically interesting aspects of the methods of socializing teachers are also discussed,
Keywords: educating; socialization; teaching profession